2019
DOI: 10.1016/j.physbeh.2019.03.029
|View full text |Cite
|
Sign up to set email alerts
|

The effect of glucagon-like peptide-1 (GLP-1) receptor agonists on substance use disorder (SUD)-related behavioural effects of drugs and alcohol: A systematic review

Abstract: Glucagon-like-peptide-1 (GLP-1)-receptor agonists have been proposed as putative treatment for substance use disorders (SUD). The objective of this systematic review is to characterize the effects of GLP-1-receptor agonists on SUD-related behavioural effects of drugs, nicotine, and alcohol.The review was performed according to Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA). A search was performed in PubMed and EMBASE on June 16, 2018. The inclusion criteria were primary studies inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 37 publications
0
13
0
Order By: Relevance
“…Data in abstract format reported that liraglutide treatment reduces alcohol intake in patients with diabetes 27 . Thus, most evidence of an effect of GLP‐1 receptor agonists on alcohol consumption is based on rodent studies 16 and studies in velvet monkeys, 28 all showing that GLP‐1 receptor agonists reduce intake of alcohol. The present study was based on the hypothesis that GLP‐1 receptor agonists attenuate the ability of alcohol to activate the mesolimbic dopamine system, and through this decreases the motivation for alcohol consumption 29,30 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Data in abstract format reported that liraglutide treatment reduces alcohol intake in patients with diabetes 27 . Thus, most evidence of an effect of GLP‐1 receptor agonists on alcohol consumption is based on rodent studies 16 and studies in velvet monkeys, 28 all showing that GLP‐1 receptor agonists reduce intake of alcohol. The present study was based on the hypothesis that GLP‐1 receptor agonists attenuate the ability of alcohol to activate the mesolimbic dopamine system, and through this decreases the motivation for alcohol consumption 29,30 .…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it is possible that the effect that is either only observed in the initial treatment phase, that is, 3 months or is caused by GLP‐1 receptor agonist‐related adverse events is due to unspecified factors, for example, more frequent contact to doctors, healthy life style advice or other lifestyle choices during this specific period of time. Most previous experimental studies have examined potential acute effects of GLP‐1 receptor agonists, while evidence on chronic or subchronic use of GLP‐1 receptor agonists and alcohol use is sparse 16 . It is thus possible that only acute but not chronic use of GLP‐1 receptor agonists affect alcohol consumption.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In support of this hypothesis, several studies have reported expression of GLP-1 receptors in brain areas associated with reward and addiction ( 6 , 9 16 ). Furthermore, treatment with GLP-1 receptor agonists reduce alcohol intake and decrease relapse-like alcohol drinking in nonhuman primates ( 17 ) and rodents ( 18 ). In humans, a recent study reported that the GLP-1 receptor 168Ser allele variant was associated with increased alcohol intake in humans ( 19 ).…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, GLP-1 has effects on the reward system ( 67 ). If overeating in obesity is viewed as a disturbance of appetite regulation, related to other forms of abuse, the GLP-1RAs might also be useful in other forms of abuse ( 68 ), and this is currently being investigated.…”
Section: Introductionmentioning
confidence: 99%